The Influence of Digital Literature on Women's Entrepreneurship Behavior in MSMEs: The Study of English Hydroid Craft Surabaya - Karina Kusumadewi; Raya Sulistyowati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study at to understand the effect of digital literacy on women's entrepreneurial behavior in SMEs of water hyacinth craft in Surabaya. The population in this study is water hyacinth artisans who are female in Surabaya. According to the data of MSMEs in the city of Surabaya, there are 17 MSMEs for water hyacinth handicrafts. The number of research samples used by researchers is a minimum of 3 samples in each of the 17 female water hyacinth artisans in the city of Surabaya to meet the assumptions in the implementation of multiple regression analysis with a minimum of 30 respondents. The data for this study was obtained through a questionnaire. The data analysis technique used in this research is descriptive analysis, validity test, reliability test, analysis prerequisite test, and hypothesis testing. Based on the results of the data analysis that has been carried out in this study, it can be concluded that based on the results of the t-test, it can be seen that Digital Literacy has a significant favorable influence on Entrepreneurial Behavior in Water Hyacinth MSMEs in Surabaya. there is an effect of variable X on Y by 63.1%, and other factors influence the remaining 36.9%.